2018
DOI: 10.1186/s12909-018-1155-9
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and career choices among physicians in Finland: employment sector, clinical patient contact, specialty and change of specialty

Abstract: BackgroundPersonality influences an individual’s adaptation to a specific job or organization. Little is known about personality trait differences between medical career and specialty choices after graduating from medical school when actually practicing different medical specialties. Moreover, whether personality traits contribute to important career choices such as choosing to work in the private or public sector or with clinical patient contact, as well as change of specialty, have remained largely unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
68
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 56 publications
(108 reference statements)
9
68
3
3
Order By: Relevance
“…Our study did not focus on anticipated prestige and income, which may be the key factor in the choice of specialty training [25]. We did not concentrate much on the personal experience of future specialists either.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not focus on anticipated prestige and income, which may be the key factor in the choice of specialty training [25]. We did not concentrate much on the personal experience of future specialists either.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant difference between the personalities of men and women in our student sample, mainly in the honest-humility, emotionality, and altruism scales; this finding is similar to the results of a study by Hojat & Zuckerman (4) , but in contrast to those obtained by Kwon & Park (7) , who found no difference between sexes in their sample. However, a study by Mullola et al (21) found that female specialists scored higher for extroversion and conscientiousness than male specialists, while Weisberg et al (22) analyzed BFM scores by sex and reported that although women had a tendency to score higher for agreeableness, extroversion, and neuroticism; there were no differences between the sexes for the conscientiousness and openness scales. These findings differ from our results indicating that female students had lower scores than men for extroversion but similar scores for conscientiousness and agreeableness.…”
Section: Discussionmentioning
confidence: 98%
“…As mulheres estão mais expostas do que os homens aos problemas físicos e mentais e uma maior tendência a estresse e insatisfação profissional no trabalho (13,14) . Porém, no atual estudo, houve uma tendência quanto ao domínio psicológico, sendo relacionada como uma das principais causas de adoecimento do médico, lembrando que a dinâmica mental interfere na qualidade de vida, visto que modifica a percepção que se tem da própria existência, sendo que médicos com perfil patológico no domínio psicológico obtém menor QV quando comparado à população em geral (15) .…”
Section: Discussionunclassified